2009
DOI: 10.1137/080717006
|View full text |Cite
|
Sign up to set email alerts
|

Multiparasitoid-Host Interactions with Egg-Limited Encounter Rates

Abstract: To address the contentious issue of multiple parasitoid introductions in classical biological control, a discrete-time model of multiparasitoid-host interactions that accounts for host density dependence and egg limitation is introduced and analyzed. For parasitoids that are egg limited but not search limited, the model is proven to exhibit four types of dynamics: host failure in which the host becomes extinct in the presence or absence of the parasitoids; parasitoid-driven extinction in which the parasitoid c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…For over 80 years, different researchers have answered this question differently. The result has been the creation of competing families of models for host–parasitoid population dynamics, one emphasizing time limitation (Lotka 1925; Nicholson and Bailey 1935; Hassell 1978, 2000; Murdoch et al 2003) and another emphasizing egg limitation (Thompson 1924, Getz and Mills 1996; Shea et al 1996; Heimpel et al 2003; Schreiber 2006, 2007; Schreiber and Vejdani 2006; Kon and Schreiber 2009), and competing families of models of insect reproductive behavior, again one emphasizing time limitation (Charnov and Skinner 1985; Visser et al 1992; Godfray 1994) and another emphasizing egg limitation (Iwasa et al 1984; Mangel 1987; Mangel and Heimpel 1998). These different classes of models often make very different predictions (e.g., Mangel 1989), underscoring the importance of resolving the relative importance of time and egg limitation.…”
mentioning
confidence: 99%
“…For over 80 years, different researchers have answered this question differently. The result has been the creation of competing families of models for host–parasitoid population dynamics, one emphasizing time limitation (Lotka 1925; Nicholson and Bailey 1935; Hassell 1978, 2000; Murdoch et al 2003) and another emphasizing egg limitation (Thompson 1924, Getz and Mills 1996; Shea et al 1996; Heimpel et al 2003; Schreiber 2006, 2007; Schreiber and Vejdani 2006; Kon and Schreiber 2009), and competing families of models of insect reproductive behavior, again one emphasizing time limitation (Charnov and Skinner 1985; Visser et al 1992; Godfray 1994) and another emphasizing egg limitation (Iwasa et al 1984; Mangel 1987; Mangel and Heimpel 1998). These different classes of models often make very different predictions (e.g., Mangel 1989), underscoring the importance of resolving the relative importance of time and egg limitation.…”
mentioning
confidence: 99%
“…For more than 80 years, researchers have put forth various models to assess whether the realized lifetime reproductive success of adult female parasitoids is constrained by the limited time available for finding oviposition sites [38][39][40][41][42], or by the finite supply of mature eggs [43,44]. Rosenheim [45] employed models to investigate how stochastic factors affect the evolution of egg limitation among insects.…”
Section: Introductionmentioning
confidence: 99%
“…For over 80 years, researchers have proposed different models to determine if the realized lifetime reproductive success of adult female parasitoids was limited by the finite amount of time available to locate hosts that serve as oviposition sites [33][34][35][36][37], or by the finite supply of mature eggs [38,39]. Rosenheim [40], using models to explore how stochasticity influences the evolution of egg limitation in insects, found that both egg and time limitations are fundamental in shaping insect reproductive behavior and population dynamics.…”
Section: Introductionmentioning
confidence: 99%